Active Supervision: An Effective, Efficient, Low-Intensity Strategy to Support Student Success. (December 2018) - Menzies, Holly M.; Lane, Kathleen Lynne; Oakes, Wendy Peia; Ruth, Karen; Cantwell, Emily D.; Smith-Menzies, Lucia
Active supervision is a practical strategy for increasing student engagement and decreasing student disruptive behavior. In this article, we describe a step-by-step process for using active supervision, with teaching tips to assist with successful implementation. Throughout the article we offer lessons from the field featuring the perspectives of practitioners who have used active supervision in classrooms that include students with challenging behavior.